PERUBAHAN SIFAT FISIK SAMPAH ORGANIK PADAT PADA PROSES PENGOMPOSAN SECARA OPEN WINDROW - Setiyo, Yohanes (Agrotekno, 2012)
This research was done with aim to identify physicalproperties changes during composting process of organicmunicipal solid waste. Bulk density, moisture content,particle size, and porosity of produced compost wereobserved every one week at three point depth of compostingprocess. Oxygen concentration at the critical point wasobserved for checking the diffusion potential of air. Thisobservation was done everyday by using Cosmotector typeXPO-318.Relation equation between bulk density, porosity andmoisture content with time of composting product weredescribed by ? = -0.0966t2 + 9.23t + 147.8 with the value ofR2 = 0.95, ? = -0.0292ln(t) + 0.745 with value of R2 = 0.944,and Mc = -0.0785ln(t) + 0.8685 with r2 = 0.95. Processshould be futher supported with a turning over of thecompost which done weekly so the availability of O2 atamount of 50 to 190 g/kg air.
Keywords: municipal solid waste, open windrow, composting